The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/978-3-319-25474-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Contralateral Efferent Reflex in Hearing Demonstrated with Cochlear Implants

Abstract: Our two ears do not function as fixed and independent sound receptors; their functioning is coupled and dynamically adjusted via the contralateral medial olivocochlear efferent reflex (MOCR). The MOCR possibly facilitates speech recognition in noisy environments. Such a role, however, is yet to be demonstrated because selective deactivation of the reflex during natural acoustic listening has not been possible for human subjects up until now. Here, we propose that this and other roles of the MOCR may be elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
2
8
0
2
Order By: Relevance
“…Some of these benefits are admittedly most obvious for this particular spatial configuration (SLNR) but still hold for other spatial configurations (not shown). Furthermore, we have shown elsewhere that similar effects occur for a speech source presented in competition with another speech source ( Lopez-Poveda 2015 ; Lopez-Poveda et al 2016 ).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Some of these benefits are admittedly most obvious for this particular spatial configuration (SLNR) but still hold for other spatial configurations (not shown). Furthermore, we have shown elsewhere that similar effects occur for a speech source presented in competition with another speech source ( Lopez-Poveda 2015 ; Lopez-Poveda et al 2016 ).…”
Section: Resultssupporting
confidence: 67%
“…We have shown that for different input signals at the two ears, the MOC strategy enhances the interaural current difference in a frequency specific manner (Fig. 3 F; see also Lopez-Poveda et al 2016 ). Therefore, one might wonder whether the better intelligibility with the MOC strategy is the result of enhanced interaural current differences rather than or in combination with the other previously mentioned positive effects, particularly with the enhanced SNR in the better ear.…”
Section: Discussionmentioning
confidence: 74%
“…Since the comparison of interaural signals is essential to accurate sound localization (Seebacher et al, 2019;Zirn et al, 2019), a delicate calibration between the signals received from the two ears must be maintained. Moreover, the efferent architecture has been shown to have a significant function in the "cocktail party effect," which refers to the ability to parse one particular auditory stream from a complex acoustic environment (Giraud et al, 1997;Kumar and Vanaja, 2004;Kim et al, 2006;Andéol et al, 2011;Smith and Keil, 2015;Lopez-Poveda et al, 2016).…”
Section: Significance Statementmentioning
confidence: 99%
“…As a result, the users of cochlear implants lack MOC efferent effects but may have the effects of LOC efferents. Therefore, insights into the roles of olivocochlear efferents in hearing may be gained by comparing auditory performance by normal-hearing individuals with that of cochlear implant users ( 199 ). In addition, cochlear implants allow unique control over the electrical stimulation used to evoke auditory sensations.…”
Section: Open Issues and Outlookmentioning
confidence: 99%